INSTALLATION OF SOLAR-POWERED LIGHTING IN CIRUMPUT VILLAGE, CUGENANG DISTRICT, CIANJUR REGENCY - Nurhayati, Immas; Al Kindi, Hablinur; Rahmat Rosyadi, Abdu; Suharti, Titing; Sutoyo, Edi (LPPM Univ. Ibn Khaldun Bogor, 2023)
the earthquake that occurred in Cianjur West Java on november 21 resulting in 327 deaths. One of the problems in Kampung Nagrog after the earthquake was lighting. Some places do not have lighting such as toilets, prayer rooms and roads. Lighting is needed because the mobility of residents and volunteers is very high after the earthquake both during the day and at night. Therefore we need a lighting source that stays on if there is a disturbance in the PLN electricity network, is environmentally friendly, and economical. The solution to the problems of Kampung Nagrog after the earthquake disaster is to install solar cell lights. Solar cell lights do not need a PLN electricity network, are environmentally friendly and economical. Solar cell lights are moveable or can be moved easily.